A Triple-Masked, Randomized Controlled Trial Comparing Ultrasound-Guided Brachial Plexus and Distal Peripheral Nerve Block Anesthesia for Outpatient Hand Surgery. (15th April 2014) - Lam, Nicholas C. K.; Charles, Matthew; Mercer, Deana; Soneru, Codruta; Dillow, Jennifer; Jaime, Francisco; Petersen, Timothy R.; Mariano, Edward R.
Abstract : Background . For hand surgery, brachial plexus blocks provide effective anesthesia but produce undesirable numbness. We hypothesized that distal peripheral nerve blocks will better preserve motor function while providing effective anesthesia. Methods . Adult subjects who were scheduled for elective ambulatory hand surgery under regional anesthesia and sedation were recruited and randomly assigned to receive ultrasound-guided supraclavicular brachial plexus block or distal block of the ulnar and median nerves. Each subject received 15 mL of 1.5% mepivacaine at the assigned location with 15 mL of normal saline injected in the alternate block location. The primary outcome (change in baseline grip strength measured by a hydraulic dynamometer) was tested before the block and prior to discharge. Subject satisfaction data were collected the day after surgery. Results . Fourteen subjects were enrolled. Median (interquartile range [IQR]) strength loss in the distal group was 21.4% (14.3, 47.8%), while all subjects in the supraclavicular group lost 100% of their preoperative strength, P = 0.001. Subjects in the distal group reported greater satisfaction with their block procedures on the day after surgery, P = 0.012. Conclusion . Distal nerve blocks better preserve motor function without negatively affecting quality of anesthesia, leading to increased patient satisfaction, when compared to brachial plexus block.